Identification and Purity Test of Melon Cultivars and F₁ Hybrids Using Fluidigm-based SNP Markers - Kishor, D.S.; Noh, Yoonji; Song, Woon-Ho; Lee, Gung Pyo; Jung, Jin-Kee; Shim, Eun-Jo; Chung, Sang-Min (Weon'ye gwahag gi'sulji, 2020)
In melon (Cucumis melo L.), the grow-out test (GOT) has been traditionally used as a genetic puritytest. However, this method is time-consuming, space-demanding, and associated with ambiguousclassification of the genotypes. Molecular markers have proved to be an efficient tool in genotypinganalyses. In the present study, a total of 96 genome-wide single nucleotide polymorphism (SNP)markers differentiated 85 melon F1 hybrid plants from their parental lines and six other PT melonbreeding lines via high-throughput Fluidigm genotyping. Of these, 39 SNP markers showed polymorphismbetween the parents. Additionally, SNP analysis and population structure analysis showed thatseveral F1 hybrid plants were associated with outcrossing during the breeding program. Unweightedpair group method with arithmetic average (UPGMA) analysis revealed that most of the contaminatedplants were closely sub-grouped with the 7_PT1 breeding line, suggesting possible outcrossingwith 7_PT1. By combining with simple DNA extraction, the Fluidigm-based SNP marker analysisproved to be a simple and effective approach for the genetic purity analysis of F1 hybrids and meloncultivars. KCI Citation Count: 3